A heat dissipation enhancing method for the high-speed spindle based on heat conductive paths. (April 2023) - Li, Yang; Yu, Maolin; Bai, Yinming; Hou, Zhaoyang; Zhang, Huijie; Wu, Wenwu
High-speed spindle systems could generate sufficient heat when they are operating and would cause thermal deformation that influences spindle accuracy. Heat dissipation is a common and effective way to remove the generated heat. In this paper, heat conductive paths were created on the bearing seat and the spindle housing along the radial direction. Along these paths, the heat was transferred directly from heat sources inside the spindle system to outside and the heat dissipation was enhanced. To limit the heat transferred along the axial direction, the inner wall of the path was coated with a thermal insulation material. Based on an annular plate model, the influences of the affecting parameters of paths on the heat transfer performance were studied. The temperature distributions of the models with and without heat conductive paths were numerically and experimentally investigated. It was found that after using heat conductive paths, the heat dissipation enhanced significantly. Moreover, it is found that as the number and diameter of paths increases, the temperature of internal parts decreases and the gap between the highest and the lowest temperature is narrowed.